New topological 3D copper(ii) coordination networks: catechol oxidation catalysis and solvent adsorption via porous properties. Issue 12 (2nd March 2015) - Kim, Doeon; Kim, Byung Joo; Noh, Tae Hwan; Jung, Ok-Sang
Abstract : New topological 3D coordination networks, [Cu3 L4 (CH3 CN)6 ](X)6, with oval-shaped pores of 11 × 11 × 25 Å 3 dimensions are good heterogeneous oxidation catalysts of catechols and reversible solvent reservoirs. Abstract : The reaction of CuX2 (X − = ClO4 − and BF4 − ) with a new 1, 3, 5-tris(isonicotinoyloxymethyl)benzene (L) ligand gives rise to 3D coordination networks, [Cu3 L4 (CH3 CN)6 ](X)6, with a new topology of the Schläfli point symbol {4·8 2 }4 {4 2 ·8 2 ·10 2 }2 {8 4 ·12 2 }. [Cu3 L4 (CH3 CN)6 ](ClO4 )6 and [Cu3 L4 (CH3 CN)6 ](BF4 )6 networks have useful oval-shaped pores of 11.2 × 11.2 × 24.8 Å 3 and 11.1 × 11.1 × 24.4 Å 3 dimensions, respectively. These porous coordination networks act as good heterogeneous catalysts, oxidizing the catechols in the order 3, 5-di- tert -butylcatechol (3, 5-DBuCat) > 4- tert -butylcatechol (4-BuCat) > 4-chlorocatechol (4-ClCat). The catalytic effect of [Cu3 L4 (CH3 CN)6 ](BF4 )6 is slightly higher than that of [Cu3 L4 (CH3 CN)6 ](ClO4 )6 . The pores of the 3D networks reversibly adsorb the solvents in the order chloroform > tetrahydrofuran > acetone.